1999
DOI: 10.1143/jjap.38.2097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sputtering Parameters on the Formation Process of High-Quality and Low-Resistivity HfN Thin Film

Abstract: We have investigated the influence of sputtering parameters such as N2 flow ratio, applied dc power and substrate temperature on the formation process of high-quality and low-resistivity HfN film using an ultrahigh-vacuum sputtering system. The obtained film quality was evaluated using X-ray diffraction, X-ray photoelectron spectroscopy and Auger electron spectroscopy analyses. The resistivity values were measured by a four-point probe method. We found that (111) HfN and (100) HfN films with equivalent resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 16 publications
3
29
1
Order By: Relevance
“…• C. [21][22][23] In our case, the possible formation of HfN can be linked with the observed out-diffusion of N, which can be understood as follows. The out diffusion of N at 600…”
Section: Ecs Journal Of Solid State Science and Technology 4 (2) P30mentioning
confidence: 79%
“…• C. [21][22][23] In our case, the possible formation of HfN can be linked with the observed out-diffusion of N, which can be understood as follows. The out diffusion of N at 600…”
Section: Ecs Journal Of Solid State Science and Technology 4 (2) P30mentioning
confidence: 79%
“…Shinkai et al 27 have demonstrated growth of single-orientation HfN on (001) and (111) Si substrates. Therefore, using HfN as a buffer layer we should be able to deposit epitaxial superlattices on Si substrates.…”
Section: Effect Of Substratesmentioning
confidence: 99%
“…Due to the small (0.02%) mismatch for the coincident-site lattice involving 6 HfN unit cells and 5 Si unit cells, HfN can be grown epitaxially on Si. 17 Like AlN, HfN is stable with regard 2 to formation of Si 3 N 4 , but should offer better diffusion resistance. Additionally, HfN is expected to form an ohmic contact to n-GaN.…”
mentioning
confidence: 99%
“…17 It is emphasized that this process was not originally intended to prepare buffer layers for GaN growth, and the 450°C HfN deposition temperature was the practical maximum for the deposition chamber rather than the optimum for HfN epitaxy. The HfN stoichiometry was confirmed by x-ray photoelectron spectroscopy and the cube-on-cube epitaxial relationship was verified by x-ray diffraction.…”
mentioning
confidence: 99%